Isoniazid-Induced Lichenoid Drug Eruption: A Rare Case Report - Rajgoli, Atiya; Tambe, Aiiravat; Tewari, Ishan; Reddy, Mandati Santhosh; Kini, Pratiksha; Doshi, Bhavana (Indian Journal of Pharmacy Practice)
Lichenoid Drug Eruption (LDE) is a rare, immune-mediated adverse cutaneous reaction that closely mimics idiopathic lichen planus. Isoniazid, a first-line anti-tubercular drug, has been infrequently implicated as a causative agent. We report the case of a 55-year-old male with hypertension and pulmonary tuberculosis receiving multidrug anti-tubercular therapy, who developed multiple hyperpigmented macules, patches, and plaques over the trunk, limbs, and oral mucosa. Histopathological examination revealed features consistent with lichenoid dermatitis. The patient was managed with systemic corticosteroids, immunosuppressants, and supportive therapy while continuing anti-tubercular treatment. This case emphasizes the importance of recognizing isoniazid-induced cutaneous adverse reactions early, managing them effectively without discontinuing essential therapy, and ensuring multidisciplinary collaboration between dermatology, pulmonology, and pharmacy teams to achieve optimal outcomes.
Keywords: Anti-tubercular Therapy; Cutaneous Adverse Drug Reaction; Isoniazid; Lichenoid; Drug Eruption